Unlocking market share growth: The role of service facilities and financial performance in Islamic Banks - Nurfadila, Belinda; Maulana, Agus (Journal of Law, Administration, and Social Science, 2025)
Indonesia, as the country with the largest Muslim population in the world, reaching 237.6 million people or 86.7% of its total population, presents a unique potential for Islamic banking. However, the market share of Islamic banks remains surprisingly low at only 7.09%. This study aims to analyze the impact of service facilities and financial performance on the market share of Islamic banks in Indonesia. Employing panel data regression analysis with Stata software at a 5% significance level, this research reveals that the number of service offices positively and significantly influences the market share, while the Operating Cost to Operating Income (BOPO) ratio has a significant negative effect. Conversely, variables such as the number of ATMs, Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Finance to Deposit Ratio (FDR) show no significant impact. These findings provide valuable insights into the factors shaping the market share of Islamic banks and underline the importance of optimizing service facilities and financial efficiency to enhance their competitive position.